From trials to the public health: pre-exposure prophylaxis for HIV prevention (Colombia Medica, 2013)
Two million two hundred thousand adults were newly HIV-infected in 2011, underscoring the urgent need for new, effective ways to prevent incident infections. Recently, the field of HIV prevention has gathered positive results from different strategies, among different populations, and with varying effect sizes, including the treatment of HIV-positive women and men in discordant couples, male circumcision of HIV-negative men in sub-Saharan Africa, a HIV vaccine evaluated in a community-based trial among HIV-negative men and women in Thailand, the use of vaginal gel formulation of TDF for HIV prevention in women in South Africa, pre-exposure prophylaxis (PrEP) with tenofovir disoproxil fumarate (TDF) or emtricitabine and TDF (TDF-FTC) among HIV-1-serodiscordant heterosexual couples from Kenya and Uganda, and PrEP with TDF-FTC among heterosexual men and women in Africa. Of these interventions, PrEP is an attractive policy because it does not directly interferes with the sexual intercourse, providing people a choice on HIV prevention regardless of cultural, religious, or social harnesses.